Penerapan Teknologi Pirolisis Secara Terpadu Dari Pemanfaatan Limbah Kayu di Desa Paccellekang - Mohammad Wijaya; Harfiana Abbas, Gusma; Yani, Setyawati; Fadly, Dewiyanti; Puji Cahyani, Vika (Pusat Riset dan Inovasi Nasional, 2025)
Natural resource management in Paccellekang Village, which includes rice paddies, plantations, and teak trees, remains suboptimal despite its significant potential, particularly the abundant wood waste. This wood waste largely originates from agricultural activities, plantations, and small-scale wood processing. Currently, this waste is often simply burned or dumped, potentially polluting the environment and causing air pollution. However, if managed properly, wood waste can be transformed into high-value products that can provide financial benefits to the community. This community service activity aims to empower farmer groups through training in processing wood waste into marketable products such as charcoal, liquid smoke, and wood flour. These products not only have economic value but are also useful in various sectors, for example, liquid smoke as a natural preservative, charcoal as an environmentally friendly fuel, and wood flour as an industrial raw material. The program implementation method uses a structured approach that includes initial observations to identify potential partners and needs, outreach to provide a comprehensive understanding of the program's objectives, and training in wood waste processing technology. Furthermore, intensive mentoring and evaluation of implementation results are provided to ensure program sustainability. The results demonstrated that the farmer group members understood the concept of productive wood waste management and demonstrated high enthusiasm for developing innovative products. This program successfully improved the community's skills in utilizing local resources while reducing the negative impact of waste on the environment. Thus, this activity contributed to increasing community income and supporting sustainable economic development in Paccellekang Village.